Transformasi Paradigma Studi Al-Qur’an dan Tafsir di Era Digital: Dialektika antara Warisan Tafsir Klasik dan Inovasi Teknologis Kontemporer - Ilmiah, Dewi Bahrotul (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2025)
The development of digital technology has had a significant impact on the dynamics of Qur'anic studies and interpretation in the academic realm. This transformation has not only changed media and learning methods but also given rise to a new paradigm that demands integration between classical scholarly traditions and digital innovation. This study aims to analyze the direction of development of Qur'anic interpretation studies in the digital era by examining how digitalization influences the production, dissemination, and methodology of Qur'anic studies in Islamic academic circles. The research method used is qualitative, with a literature study approach and content analysis of academic journals, digital interpretation platforms, and curriculum documents of Islamic universities in Indonesia and the Islamic world in general. Data are analyzed descriptively and critically to identify changing patterns, methodological tendencies, and epistemological strengthening of digitalization on the science of interpretation. The results show that integration between the classical interpretation heritage and technological innovation is key to maintaining the authenticity and validity of interpretation in the digital era. The development of digital interpretation based on classical principles is necessary to ensure that technological transformation remains aligned with the values ​​of Islamic scholarship. Epistemological integration between the legacy of classical interpretation and digital innovation needs to be developed in a balanced manner in order to produce a paradigm for Qur'anic studies that is adaptive, accountable, and contextual to the needs of the people in the modern era.